2014
DOI: 10.1016/j.jsat.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Web-based training for primary care providers on screening, brief intervention, and referral to treatment (SBIRT) for alcohol, tobacco, and other drugs

Abstract: This project evaluated a web-based multimedia training for primary care providers in screening, brief intervention, and referral to treatment (SBIRT) for unhealthy use of alcohol, tobacco, and other drugs. Physicians (n=37), physician assistants (n=35), and nurse practitioners (n=20) were recruited nationally by email and randomly assigned to online access to either the multimedia training or comparable reading materials. At baseline, compared to non-physicians, physicians reported lower self-efficacy for coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
0
42
2
6
Order By: Relevance
“…Furthermore, most or all of the proposed adaptations within the RT component may be implemented by properly trained ancillary healthcare personnel (e.g., nurse practitioners, physician assistants, behavioral health counselors) rather than by physicians. In fact, Stoner and colleagues (2014) showed that physicians, nurse practitioners, and physician assistants can be trained to implement SBIRT with equivalent levels of proficiency using self-administered online tutorials and instructional materials. The notion of utilizing non-physicians to implement the RT process is consistent with the emerging public health service policy and practice known as “task shifting” by which ancillary workers are trained to provide basic healthcare services in the face of provider shortages and other constraints on service availability and accessibility (Kazdin & Rabbitt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most or all of the proposed adaptations within the RT component may be implemented by properly trained ancillary healthcare personnel (e.g., nurse practitioners, physician assistants, behavioral health counselors) rather than by physicians. In fact, Stoner and colleagues (2014) showed that physicians, nurse practitioners, and physician assistants can be trained to implement SBIRT with equivalent levels of proficiency using self-administered online tutorials and instructional materials. The notion of utilizing non-physicians to implement the RT process is consistent with the emerging public health service policy and practice known as “task shifting” by which ancillary workers are trained to provide basic healthcare services in the face of provider shortages and other constraints on service availability and accessibility (Kazdin & Rabbitt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, e‐health care intelligence solutions enable medical practices to acquire evidence‐based medical information (Metzger & Flanagin, ; Pittler, Mavergames, Ernst, & Antes, ; Weng et al, ) such as clinical guidance systems for supportive care in diabetes (Sağlam & Temizel, ) and cancer (Van Erps et al, ). A second form of e‐learning capability is called e‐training, that is, the ability of the medical practice to provide Web‐based support for the continuing medical education of its physicians and nurses (Baker, Kamke, O'Hara, & Stuart, ; Casebeer et al, ; Chu & Robey, ; Robson, ; Samuelson et al, ; Stoner, Mikko, & Carpenter, ). The third and final form is called e‐collaboration, which consists in the ability to use Web‐based applications to create, integrate, and share clinical knowledge with other primary health care providers and stakeholders (Bassi, Lau, Hagens, Leaver, & Price, ; Paul, ; Quinn, Huckel‐Schneider, Campbell, Seale, & Milat, ), including the ability to participate in Web 2.0 virtual communities of practice (Mendizabal, Nuño‐Solinis, & González, ).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Importantly, e-health care intelligence solutions enable medical practices to acquire evidence-based medical information (Metzger & Flanagin, 2011;Pittler, Mavergames, Ernst, & Antes, 2011;Weng et al, 2013) such as clinical guidance systems for supportive care in diabetes (Sağlam & Temizel, 2014) and cancer (Van Erps et al, 2010). A second form of e-learning capability is called e-training, that is, the ability of the medical practice to provide Web-based support for the continuing medical education of its physicians and nurses (Baker, Kamke, O 0 Hara, & Stuart, 2009;Casebeer et al, 2010;Chu & Robey, 2008;Robson, 2009;Samuelson et al, 2014;Stoner, Mikko, & Carpenter, 2014).…”
Section: Conceptualization Of Research Variablesmentioning
confidence: 99%
“…Screening, brief intervention, and referral to treatment (SBIRT) for a range of substance use problems is a cost-effective, comprehensive, and integrated system of early intervention and treatment services for individuals who use tobacco, alcohol, or other drugs [9]. A review of brief, multi-contact behavioural counselling interventions among adult patients attending primary care found such interventions reduced the average number of drinks per week by 13–34 %, increased the proportion drinking at moderate or low risk levels by 10–19 %, concluding such interventions were feasible and potentially highly effective components of an overall public health approach to reducing problem alcohol use [10].…”
Section: Introductionmentioning
confidence: 99%